Effects of Different Concentrations of Arsine on the Synthesis and Final Properties of Polypropylene (2022)
This article studies the effects of arsine on the synthesis and thermal degradation of 4 sam ples of virgin polypropylene (PP-virgin) and proposes reaction mechanisms that allow understanding of its behaviour. Different points are monitored during the polypropylene synthesis to perform TGA, DSC, FT-IR, RDX, and MFI analyses later. The content of AsH3 in polypropylene varies between 0.05 and 4.73 ppm, and of arsenic in virgin PP residues between 0.001 and 4.32 ppm for PP0 and PP10, increasing in fluidity index from 3.0 to 24.51. The origin of thermo-oxidative degradation is explained by the reaction mechanisms of the Molecule AsH3 with the active titanium center of the ZN catalyst and the subsequent oxidation to form radical complexes. OO-AsH-TiCl4 -MgCl2 and (OO-as-OO)2 -TiCl4 -MgCl2 , which, by radical reactions, give rise to the formation of functional groups aldehyde, ketone, alcohol, carboxylic acid, CO, CO2 , PP-Polyol, PP-Polyether, and PP-Isopropylethers. These species caused the TG and DTG curves to increase degradation peaks in pp samples